PENGARUH SELF EFFICACY, STRES KERJA, DAN EMOTIONAL QUOTIENT TERHADAP KINERJA PERAWAT JIWA - Safitri, Novriska; Ikhram W., M. Abdi Dzil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of self-efficacy variable on mental health nurses' performance at Dr. Radjiman Wediodiningrat Lawang mental health hospital, the effect of work stress variable on mental health nurses' performance at Dr. Radjiman Wediodiningrat Lawang mental health hospital, the effect of emotional quotient variable on mental health nurses performance at Dr. Radjiman Wediodiningrat Lawang mental health hospital. This type of research is explanatory research which explains the relationship and influence between one variable and another through hypotheses testing. The data collection technique applied in this research was a questionnaire. The population of this research was 281 mental health nurses with a research sample of 74 respondents. Analysis of the data in this study using multiple linear analysis using the SPSS version 25 program. The scale used in this research is the Likert scale. The result of this research towards the third hypothesis can be concluded: self-efficacy has a positive and significant effect on mental health nurses' performance, work stress has no significant effect on mental health nurses' performance, and emotional quotient has a positive and significant effect on mental health nurses performance.